Effect of zinc supplementation on freshwater plankton density - Taneja, S K; ., Rashmi (Indian Journal of Fisheries, 2011)
The role of Zn in biological system is wellknown. However, its importance in planktonabundance has not been recognized conclusively.Accordingly, the influence of Zn onplankton density in a closed system was investigatedkeeping physico-chemical factors conduciveto them. The results are reported in thispaper.